An effective reversible data hiding algorithm using Huffman coding and pixel value prediction algorithm based on the similarity between adjacent pixel values - Mok Jung, Soo (International Journal of Engineering and Technology, 2018)
In this paper, an effective reversible data hiding algorithm was proposed to increase the amount of data to be embedded data into cover image. Generally, there is similarity between adjacent pixel values in natural images. In the proposed algorithm, a technique that accurately predicts pixel value using adjacent pixel values was used and Huffman coding algorithm was used to increase the amount of data to be embedded into cover image. The proposed reversible data hiding algorithm increases greatly the amount of data embedded into cover image. Also, the visual quality of the secrete data embedded image is very good. So, it is difficult to know whether secrete data has been embedded into the image. Also, using the proposed algorithm, secrete data can be embedded at various levels. The experimental results show that the proposed reversible data hiding algorithm is superior to APD algorithm. Therefore, the proposed algorithm is very useful for reversible data hiding applications.Â Â
Keywords: Cover Image; Data Hiding; Reversible Data Hiding; Stego-Image; Similarity.